Does Size Matter: Evaluating the Difference between Right and Left Internal Mammary Veins in Free Flap Breast Reconstruction - Mauch, Jaclyn T.; Rhemtulla, Irfan A.; Katzel, Evan B.; Hernandez, J. Andres; Broach, Robyn B.; Serletti, Joseph M. (Journal of Reconstructive Microsurgery, 2019)
Background Venous congestion in breast free flap reconstruction continues to be a major reason for flap compromise requiring reoperative exploration and possible flap failure. We aim to investigate whether size of the internal mammary vein (IMV) (1) varies between the left and right sides, (2) changes with certain patient demographics or preoperative factors, and (3) correlates with postoperative complications.Methods We performed a retrospective cohort study examining all patients undergoing free flap breast reconstruction from September 2005 to March 2016 using internal mammary recipient veins. Venous coupler size was used as a surrogate measure of IMV diameter. Preoperative patient characteristics and factors were collected. Postoperative outcomes assessed included thrombosis, flap loss, fat necrosis, and mastectomy flap necrosis. Multivariate analyses were performed to evaluate if preoperative factors affected IMV diameter and to determine if coupler size and flap side were independent risk factors for postoperative complications.Results We examined 372 patients with a total of 561 flaps. One hundred eighty-nine patients received bilateral flaps with the IMV as a recipient. The right IMV (n = 286, average = 2.97 mm, standard deviation [SD] = 0.41) was significantly larger than the left (n = 275, average = 2.89, SD = 0.35, p = 0.008). Preoperative factors and postoperative complications were not statistically different between the left and right cohorts. The multivariable linear regression model with coupler size as the dependent variable found older age trended toward a larger coupler size but this was not significant (p = 0.05). In multilinear regression analysis, the postoperative outcomes did not have significant covariates.Conclusion We found that IMV size significantly differs between the right and the left sides. However, incidence of postoperative complications was not significantly different between the left and right sides, and the multivariate analyses did not identify flap side as an independent risk factor for adverse outcomes. Prospective studies evaluating actual IMV diameter and associated complications may potentially elucidate clinical significance.
Keywords: internal mammary vein; venous coupler; autologous breast reconstruction; free flap; breast reconstruction; deep inferior epigastric artery perforator; SIEA; fTRAM; PAP; SGAP; IGAP